العلاقة بين مستويات المغنزيوم البلازمية وضبط سكر الدم عند مرضى الداء السكري من النمط الثاني - أسعد, رمال; خياط, محمد; بركات, كارولين (Latakia University Journal -Medical Sciences Series, 2018)
يعتبر الداء السكري من النمط الثاني T2DM)) أشيع الأمراض الاستقلابية التي تترافق مع عوز المغنزيوم. ونظراً للتأثيرات السلبية الناتجة عن هذا العوز فقد هدفت دراستنا إلى تقييم مستويات المغنزيوم عند مجموعة من مرضى T2DM شملت 126 مريضاً من المراجعين لمركز السكري في مدينة اللاذقية ومقارنتهم بمجموعة من الأصحاء شملت 70 فرداً، بالإضافة لدراسة علاقة المغنزيوم بالخضاب الغلوكوزي HbA1c كمشعر لضبط سكر الدم عند المرضى. تمت معايرة المغنزيوم بالطريقة اللونية Xylidyl Blue، وHbA1c بالاستشراب المبادل للشوارد، وعولجت النتائج إحصائياً باستخدام برنامج SPSS 19.0. وأظهرت النتائج انخفاض تراكيز المغنزيوم البلازمية عند المرضى مقارنة بـالأصحاء (P=0.0001)، وباعتماد المجال المرجعي للمغنزيوم البلازمي 1.9-2.5 ملغ/دل لوحظ عوز المغنزيوم عند 47.6% من المرضى و28.6% من الأصحاء، كذلك لوحظ وجود ارتباط سلبي بين مستويات Mg وHbA1c عند المرضى (r=-0.5, P=0.0002)، أي ترافقت المستويات المنخفضة للمغنزيوم مع الضبط السيء لمستويات السكر الدموية. يبرز ذلك ضرورة مراقبة تراكيز المغنزيوم عند مرضى T2DM وعند الأصحاء والمعاوضة الدوائية أو الغذائية عند حدوث العوز.Type 2 Diabetes mellitus T2DM has been suggested to be the most common metabolic disorder associated with magnesium deficiency which has many adverse outcomes. The aim of this study was to evaluate plasma Mg in 126 T2DM patients recruited from Diabetes Centre in Lattakia, compare them to 70 healthy individuals, and assess the correlation between plasma Mg and HbA1c as a glycemic control biomarker. Magnesium was measured using xylidyl blue colorimetric method. HbA1c was measured using ion-exchange resin separation. The SPSS 19.0 software was used for statistical analysis. Mean plasma Mg concentrations of the diabetics was significantly lower than controls (P=0.0001). Plasma magnesium was negatively correlated with HbA1c (r=-0.5, P=0.0002). Plasma magnesium was below the normal reference range (1.9-2.5 mg/dL) in 47.6% of diabetics and 28.6% of controls. In conclusion, it is important to monitor Mg levels in both T2DM patients and non-diabetics and take procedures to correct hypomagnesaemia states.